2001
DOI: 10.1002/ca.1028
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the extrahepatic biliary tree: Review of the world literature

Abstract: The anatomy facing a surgeon during cholecystectomy involves complex relationships between the hepatic artery, extrahepatic biliary tree, and gallbladder. A sound knowledge of the normal anatomy of the extrahepatic biliary tract is thus essential in the prevention of operative injury to it. Equally important, however, is an understanding of congenital variation of biliary and vascular anatomy, as the literature abounds with reports of specific anatomical variations, and their operative implications. This artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
1
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 39 publications
4
77
1
5
Order By: Relevance
“…Aberrant ducts which communicate the right hepatic lobe directly with the gallbladder have also been described (Foster & Wayson, 1962;Lamah et al, 2001;Cavalcanti et al) The cystic duct has three common variations: a) insertion into the distal third of the common hepatic duct (9%); b) medial insertion through the left side of the common hepatic duct (10-17%); c) course parallel to the common hepatic duct extending for 2 cm or more (1.5%-25%) according to Turner & Fulcher (2001). On the other hand, insertion of the cystic duct into the left or right hepatic ducts, or influence of the left posterior hepatic duct directly into the cystic duct are considered rare (Turner & Fulcher;Yamakawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant ducts which communicate the right hepatic lobe directly with the gallbladder have also been described (Foster & Wayson, 1962;Lamah et al, 2001;Cavalcanti et al) The cystic duct has three common variations: a) insertion into the distal third of the common hepatic duct (9%); b) medial insertion through the left side of the common hepatic duct (10-17%); c) course parallel to the common hepatic duct extending for 2 cm or more (1.5%-25%) according to Turner & Fulcher (2001). On the other hand, insertion of the cystic duct into the left or right hepatic ducts, or influence of the left posterior hepatic duct directly into the cystic duct are considered rare (Turner & Fulcher;Yamakawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This less than figures found in international data. This variation incidence varied from 8.3% to 14% in an autopsy series (Lamah 2001). In Korea, 10,243 ERCP cases were studied in a prospective way showed the cystic duct variations in 16.9% of the patients.…”
Section: Discussionmentioning
confidence: 92%
“…It is thought to be due to exuberant budding of the developing biliary tree when the caudal bud of the hepatic diverticulum divides [6,7].On the other side choledochal cysts are also rare, with an incidence of 1:100000-1500008. [2].…”
Section: Discussionmentioning
confidence: 99%
“…Senecail et al found morphologic variations and abnormalities in more than 33% but only 3 cases of real duplication from ultrasonographic exploration of the gallbladder performed on 1823 patients [8]. Anatomic variants of gallbladder duplication are still differentiated according to Boyden's classification as follows ( Figure 5) [1,6]:Choledocal cyst classification commonly accepted is one devised by Todani et al (Figure 6), that 5 main types are described.…”
Section: Discussionmentioning
confidence: 99%